(untitled) (Bangladesh Journal of Plant Taxonomy, 2020)
Grapevine is one of the major fruit trees in the Kingdom of Saudi Arabia. This study aims to discriminate and assess the genetic diversity in three grapevine cultivars in Al- Madinah through the combination of characterization using both classical ampelographic as well as ampelometric studies with molecular markers using Randomly Amplified Polymorphic DNA (RAPD), Inter Simple Sequence Repeat (ISSR) and Start Codon Targeted Polymorphism (SCoT). For the ampelographic analysis, twelve OIV descriptors were used, and for the ampelometric analysis, the fully expanded mature leaves area were automatedly measured. The genetic distance among the three grapevines cultivars, calculated using Jaccard’s coefficient, ranged from 0.7577 (between AL Nakheel and Banati) to 0.4501 (between AL Nakheel and Ahmer). The molecular analysis was based on the use of thirty-one primers; ten RAPD primers, seven ISSR primers and fourteen SCoT primers. RAPD primers generated the highest polymorphism (67%), while the level of polymorphism with ISSR primers was 36% and with SCoT 44%. All of the three markers generated similar dendrograms, and the genetic distance generated with RAPD was higher compared with SCoT and ISSR. The three markers RAPD, ISSR and SCoT were combined and amalgamated with the morphological data, and combined dendrogram was generated and discussed. AL Nakheel and Ahmer cultivars were found to be more closely related to each other than Banati which was separated in a different cluster. Both methods were effectively efficient for complete identification of grapevine and for studying the genetic diversity between closely related cultivars. Bangladesh J. Plant Taxon. 27(1): 113-127, 2020 (June)